Concept of Deradicalization against Criminal Acts of Terrorism in the Perspective of Islamic Criminal Law - Sumiadi; Zul Akli; Harley Agustian As-Samawi (Lembaga Pusat Studi Sosial dan Humaniora [LPS2H], 2025)
The phenomenon of radicalism and terrorism is a multidimensional global threat that demands a comprehensive response, not only from the repressive aspect, but also preventive and rehabilitative. This article analyzes the concept of deradicalization from the perspective of Islamic criminal law by focusing on the foundation of sharia, the role of ta'zir, the significance of ishlah and tawbah, as well as contemporary fiqh perspectives. The research shows that the principles of Islamic law, such as maqasid sharia, amar ma'ruf nahi munkar, rahmah, justice, and the concept of discretionary sanctions, provide a strong framework for de-radicalization programs. The article argues that Islam, with its emphasis on the betterment of the individual and society, offers internally relevant and humane solutions in countering extremism.